Viability of Herbal Treatments for Bacterial Wound Infections - Paudyal, Rabin; Acharya, Samikshya; Adhikari, Roji; Syangten, Reshu; Khanal, Manjula; Pathak, Binita (Tribhuvan University Journal of Microbiology, 2024)
Objectives: This study was conducted to investigate whether the commonly used kitchen spices can be used as a potential source of antimicrobial agents or not. Methods: The three spice extracts (aqueous, methanolic and ethanolic) of cinnamon, black pepper, turmeric, ginger and clove were prepared for their antimicrobial properties against common bacteria. Antimicrobial susceptibility testing was done by Well Diffusion Method on Muller Hinton Agar (MHA). Then the plates were incubated at 37°C for 24 hours. The zone of inhibition for each spice was measured. For Minimum Inhibitory Concentration (MIC), the crude extracts of ethanolic extract of clove were considered as having 100% concentration of antimicrobials. The extract was then diluted in Mueller Hinton broth serially. Standard Suspension of test organism was kept in each dilutions and incubated at 37°C for 24 hours. The highest dilution of extract showing inhibition of growth was considered as MIC. Results: In comparison to all extract, the methanolic extract of ginger showed the largest zone of inhibition (3.6 cm) against Escherichia coli. Similarly, ethanolic extract of clove was the most effective against E. coli with the zone of inhibition (3 cm). In aqueous extraction, clove showed higher antimicrobial activity against Staphylococcus aureus (1.9 cm) and cinnamon was effective against Klebsiella spp. (1.9 cm). Among all the extracts, aqueous extract generally exhibited lower antimicrobial activity. The MIC of ethanolic extract of clove against S. aureus, Bacillus spp., Klebsiella spp. and E. coli found to be the dilutions 1: 0.78, 1: 0.048, 1:0.39 and 1:1.56, respectively. Conclusion: This study concludes that clove and ginger extracts could be potential source of antimicrobials that could be used for treatment of bacterial wound infections.